Cadmium Telluride Nanocomposite Films Formation from Thermal Decomposition of Cadmium Carboxylate Precursor and Their Photoluminescence Shift from Green to Red - Rocco Carcione; Francesca Limosani; Francesco Antolini (Crystals, 2021)
This study focuses on the investigation of a CdTe quantum dots (QDs) formation from a cadmium-carboxylate precursor, such as cadmium isostearate (Cd(ISA)2), to produce CdTe QDs with tunable photoluminescent (PL) properties. The CdTe QDs are obtained by the thermal decomposition of precursors directly in the polymer matrix (in situ method) or in solution and then encapsulated in the polymer matrix (ex situ method). In both approaches, the time course of the CdTe QDs formation is followed by means of optical absorption and PL spectroscopies focusing on viable emission in the spectral interval between 520 and 630 nm. In the polymeric matrix, the QDs formation is slower than in solution and the PL bands have a higher full width at half maximum (FWHM). These results can be explained on the basis of the limited mobility of atoms and QDs in a solid matrix with respect to the solution, inducing an inhomogeneous growth and the presence of surface defects. These achievements open the way to the exploitation of Cd(ISA)2 as suitable precursor for direct laser patterning (DPL) for the manufacturing of optoelectronic devices.